2016
DOI: 10.1161/circep.116.004227
|View full text |Cite
|
Sign up to set email alerts
|

Readthrough-Promoting Drugs Gentamicin and PTC124 Fail to Rescue Na v 1.5 Function of Human-Induced Pluripotent Stem Cell–Derived Cardiomyocytes Carrying Nonsense Mutations in the Sodium Channel Gene SCN5A

Abstract: Background-Several compounds have been reported to induce translational readthrough of premature stop codons resulting in the production of full-length protein by interfering with ribosomal proofreading. Here we examined the effect of 2 of these compounds, gentamicin and PTC124, in human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes bearing nonsense mutations in the sodium channel gene SCN5A, which are associated with conduction disease and potential lethal arrhythmias. Methods and Results-We ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…Compared to the use of I Na as a single parameter, action potential can re ect the impact of variants on the entire cellular electrophysiology, including the compensation of other ion channels to the sodium current impairment. Our study illuminated the abnormality in AP pro les of BrS-CMs, which is in line with previous studies (25). The BrS-CMs also presented a prolonged AP duration, which seems to be an overlapping feature of long QT type 3 and BrS (26) (27).…”
Section: Electrophysiological Abnormalities Caused By Na V 15 Gene Vsupporting
confidence: 92%
“…Compared to the use of I Na as a single parameter, action potential can re ect the impact of variants on the entire cellular electrophysiology, including the compensation of other ion channels to the sodium current impairment. Our study illuminated the abnormality in AP pro les of BrS-CMs, which is in line with previous studies (25). The BrS-CMs also presented a prolonged AP duration, which seems to be an overlapping feature of long QT type 3 and BrS (26) (27).…”
Section: Electrophysiological Abnormalities Caused By Na V 15 Gene Vsupporting
confidence: 92%
“…The abnormal cellular behaviour was corrected by gene editing of the mutation. In a second recent study, Kosmidis and colleagues studied two nonsense mutations in SCN5A and also found reduced sodium currents and slower AP upstroke velocity ( Kosmidis et al, 2016 ). Interestingly, readthrough therapy restored function to the channels in HEK293 cells but not hiPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in a recent study using hiPSC-derived cardiomyocytes from 2 patients who harbored nonsense mutations in the sodium channel gene SCN5A, R1638X and W156X, although the premature stop codon sequences in both mutations were the most optimum sequence for PTC124, UGA, PTC124 and gentamicin, another premature stop codon read-through agent, failed to restore sodium current I Na . 34 Although the sodium channel protein level was not quantified to document the restored protein translation, other downstream mechanisms such as a trafficking defect might have been responsible. This reinforces the need for precision medicine.…”
Section: Original Researchmentioning
confidence: 99%